2022
DOI: 10.3389/fmolb.2022.903075
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings on the role of wild-type and mutant p53 in cancer development and therapy

Abstract: The p53 protein is a tumor suppressor encoded by the TP53 gene and consists of 393 amino acids with four main functional domains. This protein responds to various cellular stresses to regulate the expression of target genes, thereby causing DNA repair, cell cycle arrest, apoptosis, metabolic changes, and aging. Mutations in the TP53 gene and the functions of the wild-type p53 protein (wtp53) have been linked to various human cancers. Eight TP53 gene mutations are located in codons, constituting 28% of all p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Different studies have shown that atypical ferroptosis is either increased or decreased in osteosarcoma. Six studies ( Bouchalova et al, 2014 ; Xie et al, 2016 ; Gnanapradeepan et al, 2018 ; Su et al, 2022 ; Babamohamadi et al, 2022 ) have reported that atypical ferroptosis is enhanced in osteosarcoma. Table 4 summarizes the regulatory mechanisms of p53 on atypical ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have shown that atypical ferroptosis is either increased or decreased in osteosarcoma. Six studies ( Bouchalova et al, 2014 ; Xie et al, 2016 ; Gnanapradeepan et al, 2018 ; Su et al, 2022 ; Babamohamadi et al, 2022 ) have reported that atypical ferroptosis is enhanced in osteosarcoma. Table 4 summarizes the regulatory mechanisms of p53 on atypical ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the outcomes reported in Table 4 and the pathway illustrated in Figure 7 , we could deduce two possibilities from the regulatory outcomes of p53: enhanced ferroptosis or inhibited ferroptosis ( de Azevedo et al, 2019 ). Several studies ( Bouchalova et al, 2014 ; Xie et al, 2016 ; Gnanapradeepan et al, 2018 ; Su et al, 2022 ; Babamohamadi et al, 2022 ) have indicated that upregulation of p53 enhances atypical ferroptosis in the course of osteosarcoma, whereas other studies ( Komori, 2016 ; Van Maerken et al, 2014 ; Pang et al, 2020 ; Saraf et al, 2018 ; Yang and Zhang, 2013 ; Leroy et al, 2017 ) have reported that inactivation of p53 downregulates atypical ferroptosis in osteosarcoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the biallelic context, when VAF-adjusted is ~50%, the presence of a non-functional TP53 protein can affect the function of the wild-type TP53, contributing to tumor progression (e.g., variants present in the oligomerization domain). [94][95][96] As none of the cases presented a germline variant classified as likely oncogenic or oncogenic in TP53, it can be presumed that somatic alterations in TP53 could be drivers of tumorigenesis. This hypothesis is also corroborated by the high frequency of TP53 somatic variants in premalignant lesions of the epithelium of the ovarian or fallopian tube.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, most of the somatic variants (28/36) categorized as non‐functional or likely non‐functional presented a VAF‐adjusted ≥50%, indicating a prevalence of tumoral cells with non‐functional TP53 . In the biallelic context, when VAF‐adjusted is ~50%, the presence of a non‐functional TP53 protein can affect the function of the wild‐type TP53 , contributing to tumor progression (e.g., variants present in the oligomerization domain) 94–96 . As none of the cases presented a germline variant classified as likely oncogenic or oncogenic in TP53 , it can be presumed that somatic alterations in TP53 could be drivers of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%